2022
DOI: 10.2147/ppa.s345258
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life of Rosacea Patients in China Assessed by Dermatology Life Quality Index and Willingness to Pay

Abstract: Purpose Rosacea is a chronic inflammatory dermatosis mainly involving facial skin, leading to physical and emotional problems, which greatly affect the quality of life (QoL) of patients. Dermatology Life Quality Index (DLQI) and willingness to pay (WTP) are well-established instruments assessing the health-related quality of life (HRQoL), while very few studies have been focused on this topic about rosacea in China. The present study investigated HRQoL in Chinese rosacea patients. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
(62 reference statements)
0
9
2
Order By: Relevance
“…A recent study by Huang et al . 24 reported that the WTP for controlling rosacea among Chinese patients was $66, slightly lower than the findings in this study.…”
Section: Discussioncontrasting
confidence: 92%
“…A recent study by Huang et al . 24 reported that the WTP for controlling rosacea among Chinese patients was $66, slightly lower than the findings in this study.…”
Section: Discussioncontrasting
confidence: 92%
“…From the 207 articles identified in the literature search, 139 were excluded based on the exclusion criteria, leaving 68 publications 20–87 for the further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Another generic HRQoL instrument EuroQoL (EQ)‐5D 55,67 and its modifications EQ‐5D‐3L 76 and EQ‐5D‐visual analogue scale 77 were also used to assess quimp in rosacea. The dermatology‐specific Dermatology Life Quality Index (DLQI) was used for quimp assessment in 45 studies on rosacea 20–23,25,28–30,32,34,35,37,40–42,46,48–57,60,62–69,72–74,77,78,80,82,83,86,87 . Data on the DLQI scores from included articles is given in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of studies have shown an increased risk of anxiety and depression and impaired QOL in patients with rosacea. [20][21][22][23][24] The clinical features are heterogeneous, so the burden of the disease it causes may vary. However, the complex relationship between rosacea severity and QOL and mental health has not been examined in depth.…”
Section: Introductionmentioning
confidence: 99%